2013
DOI: 10.1021/np300751m
|View full text |Cite
|
Sign up to set email alerts
|

Meroterpenoid Pigments from the Basidiomycete Albatrellus ovinus

Abstract: Eight grifolin derivatives, involving three new monomers, albatrelins A-C (1-3), three novel dimers (meroterpenoid pigments), albatrelins D-F (4-6), and two known ones, 6a,7,8,9,10,10a-hexahydro-3,6,9-trimethyl-6-(4-methyl-3-penten-1-yl)-1,9-epoxy-6H-dibenzo[b,d]pyran (7) and confluentin (8), were isolated from Albatrellus ovinus. Their structures were established by extensive spectroscopic analysis. The absolute configurations of compounds 2-4 were determined as 9R by comparing their optical rotations with da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 16 publications
1
13
0
Order By: Relevance
“…A SciFinder search for indole-diterpenoids or meroterpenoids from Basidiomycota yielded no hits for the first class and less than 10 results that described the isolation of compounds that contain an aromatic ring attached to an acyclic farnesyl chain (e.g., [236]). These two groups of natural products may therefore not play an important role in Basidiomycota.…”
Section: Terpenoids Of Mixed Biogenetic Originmentioning
confidence: 99%
“…A SciFinder search for indole-diterpenoids or meroterpenoids from Basidiomycota yielded no hits for the first class and less than 10 results that described the isolation of compounds that contain an aromatic ring attached to an acyclic farnesyl chain (e.g., [236]). These two groups of natural products may therefore not play an important role in Basidiomycota.…”
Section: Terpenoids Of Mixed Biogenetic Originmentioning
confidence: 99%
“…frondosa resulted in the isolation of two new sterols, (22E)-ergosta-7,9(11),22-triene-3b,5a,6b-triol (111) and 3b,5a,6b-trihydroxy-(22E)-ergost-22-en-7-one (112) (Fig. frondosa resulted in the isolation of two new sterols, (22E)-ergosta-7,9(11),22-triene-3b,5a,6b-triol (111) and 3b,5a,6b-trihydroxy-(22E)-ergost-22-en-7-one (112) (Fig.…”
Section: Sterols Bearing Enone Diene and Ketone Moietiesmentioning
confidence: 99%
“…1.24) [110]. Liu et al [111] reported the isolation of six new meroterpenoids, albatrelins A-F (146-151), together with two known ones (152, 153) from Al. Liu et al [111] reported the isolation of six new meroterpenoids, albatrelins A-F (146-151), together with two known ones (152, 153) from Al.…”
Section: Meroterpenoidsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous chemical investigations of the fungi led to the isolation of a number of trilinolein, carbohydrade, stearic acid, and allantoin . In our search for structurally interesting and biologically active natural products from higher fungi, three new yellow alkaloids xylanigripones A – C ( 1 – 3 ), together with three known alkaloids ( 4 – 6 ) were isolated from the fruiting bodies of Xylaria nigripes ( Kl .) Sacc ( Fig.…”
Section: Introductionmentioning
confidence: 99%